Cryoablation for Ventricular Tachycardia Originating from Anterior Papillary Muscle of Left Ventricle Guided by Intracardiac Echocardiography - Ibrahim Marai; Nizar Andria; Osnat Gurevitz (Case Reports in Cardiology)
Papillary muscles (PMs) were reported to be origin of ventricular arrhythmia (VA). Radiofrequency (RF) ablation was reported to be acutely effective in eliminating VA. However, the recurrence rate is high. Recently, cryoablation guided by intracardiac echocardiography, 3-dimensional mapping system, and image integration was introduced as alternative strategy for this challenging ablation. We present a case of ventricular tachycardia originating from anterior PM of left ventricle treated by cryoablation guided only by intracardiac echocardiography.